Seasonal changes in Hermit Thrush (Catharus guttatus) song syntax - Sean P. Roach; Luke C. McLean; Jeff W. MacLeod; Leslie S. Phillmore (Avian Research)
In many songbird species, birdsong features phonological syntax, meaning that the units within their vocal sequences are ordered in a non-random way that adheres to a rule. While such syntactical patterns have been richly described in many species, comparatively little is known about how those patterns contribute to song achieving its important functions. For each of song's main functions, territorial defense and mate attraction, evidence of a role for syntax is limited. One species for which syntax has been thoroughly described is the Hermit Thrush (Catharus guttatus), which presents song types from their repertoires in a semi-predictable order and, in doing so, rapidly cycle up and down the frequency spectrum. The objective of the present study was to explore the importance of song syntax in the Hermit Thrush through a within-subject examination of how measures of syntax, such as the predictability of song type order within song sequences, shift over the breeding season. We hypothesized that, if such syntactical characteristics are important to breeding behaviour, they would be most prominent at the start of the breeding season when activity associated with territory establishment and mate attraction is most intense. Analysis revealed that, as predicted, the rigidness of song type ordering within sequences was highest at the start of the season and declined thereafter. That song type sequences were most predictable at the vitally important early part of the breeding season fit our hypothesis that this aspect of song syntax is important to song's functions related to territory establishment and/or mate attraction. Future work will clarify whether that role relates to one of song's two main functions or serves song transmission in some broader way.